Heavy Metal Contamination and Physicochemical Characteristics of Soils from Automobile Workshops in Abraka, Delta State, Nigeria - Anapuwa, Osakwe Stephen (International Journal of Natural Sciences Research, 2014)
Soils samples were collected from selected automobile workshops in Abraka, Delta State, Nigeria, at the depths of 0 – 15cm, 15 – 30cm and 30 – 45cm representing top,- sub- and bottom soils respectively and also from control site and 20m away from the point of impact. The soils were analyzed for their physicochemical characteristics and heavy metal levels. The pH values of the soils in all the sites ranged from 3.6 to 6.7 with mean value of 5.97 showing that the soils were moderately acidic. The electrical conductivities of the soils ranged from (µScm-1 ) 202.0 to 478.0 with mean value of 306.28 indicating significant presence of soluble inorganic substances with their corresponding ions. Total Organic Carbon content ranged from (%) 29.56 to 77.76 with mean value of 42.07 signifying presence of degradable substances and increased microbial activities in the soil. Total nitrogen contents ranged from (%) 2.03 to 9.35 with mean value of 4.19 which may be attributed to presence of some organic matters. Soil textural classification showed that the soils were sandy loamy. The heavy metal levels had the mean values of (mgkg-1) 40.05 for Fe, 16.74 for Zn, 34.39 for Mn and 0.66 for Cu showing the abundance trend of Fe>Mn>Zn>Cu. The Relative Pollution Potential and contamination/Pollution Index values revealed that the soils were slightly contaminated by heavy metals. Although the present level of heavy metal contamination of the soils does not call for any alarm, proactive steps must be taken to minimize gradual accumulation of these metals. It is hereby recommended that a separate portion of land be set apart for automobile workshops which can be called mechanic village as it is in some cosmopolitan areas in this country.